Circular villages of the Monongahela tradition - Means, Bernard K. (Bernard Klaus), 1964- (University of Alabama Press, 2007)
Between A.D. 1000 and 1635, the inhabitants of southwestern Pennsylvania and portions of adjacent states - known to archaeologists as the Monongahela Culture or Tradition - began to reside regularly in ring-shaped village settlements. These circular settlements consisted of dwellings around a central plaza. A cross-cultural and cross-temporal review of archaeological, ethnohistorical, and ethnographic cases demonstrates that this settlement form appeared repeatedly and independently worldwide, including throughout portions of the Eastern Woodlands, among the Plains Indians, and in Cent.